Discriminative Transition Sequences of Origami Metamaterials for Mechanologic. (9th December 2022) - Liu, Zuolin; Fang, Hongbin; Xu, Jian; Wang, Kon-Well
Abstract : Transitions of multistability in materials are exploited for various functions and applications, such as spectral gap tuning, impact energy trapping, and wave steering. However, a fundamental and comprehensive understanding of the transitions, either quasistatic or dynamic transitions, has not yet been acquired, especially in terms of the sequence predictability and tailoring mechanisms. This research, utilizing the stacked Miura‐ori‐variant (SMOV) structure that has multistable shape reconfigurability as a platform, uncovers the deep knowledge of quasistatic and dynamic transitions and proposes the corresponding versatile formation and tuning of mechanical logic gates. Through theoretical, numerical, and experimental means, discriminative and deterministic quasistatic transition sequences, including reversible and irreversible ones, are uncovered, where they constitute a transition map that is editable upon adjusting the design parameters. Via applying dynamic excitations and tailoring the excitation conditions, reversible transitions between all stable configurations become attainable, generating a fully connected transition map. Benefiting from the nonlinearity of the quasistatic and dynamic transitions, basic and compound mechanical logic gates are achieved. The versatility of the scheme is demonstrated using a single SMOV to realize different complex logic operations without increasing structural complexity, showing its unique computing power and inspiring the avenue for efficient physical intelligence. Abstract : With innovation that reveals the predictability and discriminability of the quasistatic and dynamic transition sequences, new knowledge of the transition mechanics is created. Moreover, the unique mechanical computing strength of the transition sequences for conducting logic operations is uncovered. Basic and various compound logic gates are achievable with a single stacked Miura‐ori‐variant structure.